2023
DOI: 10.1371/journal.pgph.0001156
|View full text |Cite
|
Sign up to set email alerts
|

Identity and COVID-19 in Canada: Gender, ethnicity, and minority status

Abstract: Background During the COVID-19 pandemic, growing evidence from the United States, the United Kingdom, and China has demonstrated the unequal social and economic burden of this health crisis. Yet, in Canada, studies assessing the socioeconomic and demographic determinants of COVID-19, and how these determinants vary by gender and ethnic minority status, remain scarce. As new strains of COVID-19 emerge, it is important to understand the disparities to be able to initiate policies and interventions that target an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Although speculative, this combination of income- and employment-related factors is likely to represent an underlying association between people’s occupational status and susceptibility to long COVID. For example, people working in front-line or essential jobs are more likely to be exposed to COVID-19, and therefore, be at greater risk of developing long COVID [ 5 ], and some research has shown that an increase in income level is significantly associated with the decreased reporting of COVID-19 symptoms [ 29 ]. Taken together, and consistent with previous research, these factors point to the complex relationship between demographic and socioeconomic circumstances and long COVID and suggest the presence of psychological and psychosocial vulnerabilities affecting recovery [ 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although speculative, this combination of income- and employment-related factors is likely to represent an underlying association between people’s occupational status and susceptibility to long COVID. For example, people working in front-line or essential jobs are more likely to be exposed to COVID-19, and therefore, be at greater risk of developing long COVID [ 5 ], and some research has shown that an increase in income level is significantly associated with the decreased reporting of COVID-19 symptoms [ 29 ]. Taken together, and consistent with previous research, these factors point to the complex relationship between demographic and socioeconomic circumstances and long COVID and suggest the presence of psychological and psychosocial vulnerabilities affecting recovery [ 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, and consistent with previous research, these factors point to the complex relationship between demographic and socioeconomic circumstances and long COVID and suggest the presence of psychological and psychosocial vulnerabilities affecting recovery [ 8 , 30 ]. Given the increasing evidence from international research demonstrating inequalities in the social and economic burdens caused by COVID-19 [ 9 , 29 , 31 , 32 ], comprehensive analyses of the effects of long COVID on ethnic and other minority groups worldwide are necessary to ensure that these groups receive accessible and appropriate access to care.…”
Section: Discussionmentioning
confidence: 99%